The Effectiveness of Physical Education Health and Recreation Learning in the Limited Face-to-Face Period - Agung Al Amin; Oki Candra (CV. AFDIFAL MAJU BERKAH, 2022)
The aim of this research is to find out the effectiveness of PJOK learning in limited face-to-face sessions at SMAN 8 Mandau. This type of research is ex-post facto research, ex-post facto research is a systematic empirical investigation in which the researcher does not control the independent variables directly because the existence of these variables has occurred or because the variables are basically not manipulated. The research was conducted at SMAN 8 Mandau on all students of class XI Mipa. SMAN 8 Mandau is located right in the town of Duri so it's easy to reach the location. The time used to carry out this research is starting from July 2022 to August 2022. The sampling is carried out by Total Sampling, where the population is used as the overall sample which amounts to class XI MIPA SMAN 8 Mandau, totaling 178 people. The instrument that will be used in this study is a questionnaire or questionnaire in conducting a survey on the effectiveness of PJOK learning in a limited face-to-face period using the Guttman Scale. Based on the calculation of the average score of the overall learning effectiveness of 66%. The scoring criteria of 63% are in the range of values ​​between 48%-79% with Good Category. This means that the effectiveness of PJOK learning in the limited face-to-face period at SMAN 8 Mandau is very effective even though there are some or a small number of students who do not like sports lessons.